ANALISIS AKUNTABILITAS PENGELOLAAN ALOKASI DANA DESA DI DESA PANTAI OA KECAMATAN WULANGGITANG KABUPATEN FLORES TIMUR - Dekrita, Yosefena Andia; Wisang, Imelda Vigula; Selan Uran, Theresia Noviyanti (AKSIOMA : Jurnal Manajemen, 2022)
Village Fund Allocation is a fund that the district government must allocate for villages originating from the central and regional financial balance funds received from the district, which use 30% for operational expenditures and 70% for community empowerment. This study aims to determine the Accountability of Village Fund Allocation Management. The type of research used is qualitative research with a descriptive analysis approach. Data collection techniques used are interviews, documentation, and literature study. The data sources of this research are primary data and secondary data (documents and archives of Pantai Oa village). The data analysis technique in this study begins with the data reduction stage, data presentation, and conclusion. The research results in the coastal village of Oa show that the management of the Village Fund Allocation from the planning, implementation, reporting, administration, and accountability stages is by Permendagri No. 113 of 2014. The Village Government of Pantai Oa has also been accountable to the region by submitting a report on the Realization of the Village Revenue and Expenditure Budget and installing billboards in front of the village office as a form of accountability to the community. Based on the results of this study, the Management of Village Fund Allocation in Pantai Oa Village can be said to be accountable. Suggestions for the village government to continue improving and maintaining the village government's performance in managing the Village Fund Allocation from each stage in the current period.